Political attitude change over time following COVID-19 lockdown: Rallying effects and differences between left and right voters - Satherley, Nicole; Zubielevitch, Elena; Greaves, Lara M.; Barlow, Fiona Kate; Osborne, Danny; Sibley, Chris G. (Frontiers in Psychology, 2022)
Restrictions to curb the spread of COVID-19 have required widespread compliance over long periods, but citizens’ attitudes to these often change over time. Here, we examine the time course of political attitudes in New Zealand over the months before and after the announcement of the country’s first nationwide COVID-19 lockdown in 2020 using a large-scale national survey (Ns = 41,831-42,663). Government satisfaction increased immediately following the lockdown announcement and remained elevated 5 months later. Trust in institutions and political efficacy also increased gradually over the same period. However, these trends varied by political party vote: Compared to center-left voters who supported the largest governing party, center-right voters who supported the opposition party returned to baseline levels of government satisfaction quicker and showed more pronounced dips in their satisfaction with the economy. These same attitudes also predicted compliance with COVID-19 guidelines. Results illustrate a rally-around-the-flag effect during the pandemic and suggest that support wanes faster among center-right (opposition party) voters.